Blacks of Tunis in al-Timbuktawi's Hatk al-Sitr: a West African jihadist's perspectives on Bori, religious deviance, and race and enslavement in Ottoman Tunisia : with translation and critical edition - Montana, Ismael Musah (Modern intellectual trends, 2024)
"While in the Ottoman Regency of Tunis after returning from pilgrimage around 1809 C.E., the Timbuktu cleric and religious puritanist, Ahmad b. al-Qadi b. Yusuf b. Ibrahim al-Fulani al-Timbuktawi wrote Hatk al-Sitr 'amma 'alayhi sudan Tunis min al-kufr (Piercing the Veil: Being an Account of the Infidel Religion of the Blacks of Tunis), which he dedicated to the ruler of the Beylic, Hammuda Pasha (r. 1782-1814 C.E.) In this treatise, al-Timbuktawi provided a vivid account of the Hausa Bori cult and entreated Tunisian authorities to imprison or even re-enslave its practitioners whom he distinguished from the heterogeneous Black population in the Regency. This critical edition and complete translation of Hatk al-Sitr places the story of al-Timbuktawi's encounter with the Bori practitioners not just in their Maghribi and Sudanic African contexts, but also in the environment of the late eighteenth and nineteenth centuries Jihad and Islamic revivalism. The result is an insight into a discourse on Bori, jihad, and race and enslavement in the context of the African Diaspora to the Islamic World"--